2011
DOI: 10.1002/j.1532-2149.2011.00063.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in perception and brain activation following stimulation by large versus small area cutaneous surface electrodes

Abstract: The current study gives evidence that CPE activates the nociceptive brain areas to a greater extent than conventional surface electrode. Therefore, CPE should preferentially be utilized in future studies where electrical stimuli are used to study nociception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 37 publications
(48 reference statements)
4
52
0
Order By: Relevance
“…Several studies have demonstrated selective activation of small fibers using intraepidermal and small surface electrical stimulation and large fibers using large surface electrical stimulation . Previously, Lelic et al . found that, when stimulating with this cutaneous pin electrode at up to 10 times the perception threshold, the brain areas processing nociceptive input were activated to a greater extent than when compared with stimulation with a large area surface electrode.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Several studies have demonstrated selective activation of small fibers using intraepidermal and small surface electrical stimulation and large fibers using large surface electrical stimulation . Previously, Lelic et al . found that, when stimulating with this cutaneous pin electrode at up to 10 times the perception threshold, the brain areas processing nociceptive input were activated to a greater extent than when compared with stimulation with a large area surface electrode.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have demonstrated selective activation of small fibers using intraepidermal and small surface electrical stimulation and large fibers using large surface electrical stimulation . Previously, Lelic et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subjectively, this induces a more localized, sharp and painful sensation. In a recent study we showed that brain sources generating the EPs were more nociceptive‐like for the intracutaneous electrode as compared with surface electrodes . Yet it can still be argued that intracutaneous electrical stimulation will likely stimulate an unselective spectrum of nerve fibres in a similar fashion to transcutaneous electrical stimulation .…”
Section: Discussionmentioning
confidence: 99%